ANALISIS BUTIR SOAL PENILAIAN AKHIR SEMESTER GASAL KELAS VII MATA PELAJARAN SIRAH NABAWIYAH DI MADRASAH QUR'ANIYAH AL HUSNAYAIN SURAKARTA TAHUN PELAJARAN 2021/2022 - Sri Mulyani; Joko Subando; Indah Nurhidayati (Al'Ulum Jurnal Pendidikan Islam, 2021)
This study aims to analyze the Sirah Nabawiyah class VII items at Madrasah Qur'aniyah Al Husnayain Surakarta at the end of the odd semester assessment for the 2021/2022 academic year in terms of the level of difficulty, discriminating power and the functioning of distractors (effectiveness of distractors) questions. This study uses a quantitative descriptive approach, the technique used is the documentation method to obtain data on eam questions, answer keys and answer sheets for class VII students, totaling 23 students. The number of questions analyzed were 25 multiple choice questions. Analisis of the data using the Anates version 4. The results of the research conducted showed (1) in terms of the level of difficulty of the question there were a 1 question (4%) included in the difficult category, 6 questions (24%) in the medium category, 5 questions (20%) including questions which is easy, 13 questions (52%) are classified as very easy questions; (2) based on discriminatory power, there is 1 questions (4%) in the very bad category because the results are negative, 14 questions (56%) are in the bad category, 3 questions (12%) included in the sufficient category and 7 questions (28%) had good discriminating power (3) in terms of distractor function (effectivity of distractors), there were 15 questions with poor distractor effectiveness, 5 questions with fairly good distractor effectiveness and 5 items having effectiveness good distractors.